Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil - Hernández-García, Luis Manuel; Burgos-Guerrero, Jesús Enrique; Rousseau, Guillaume Xavier; James, Samuel Wooster (Zootaxa, 2018)
We describe two new species from two new genera of Ocnerodrilidae from Alcântara and Rosário counties of Maranhão, Brazil. They were collected in very sandy soil in the transition between the Amazonia and Cerrado biomes. One of the species, Brasilisia punki n. sp., is the first report of earthworms of this family with an unusual pattern of genital markings and a gizzard in segment five. The other species Arraia nelmae n. sp. has a gizzard in segment six and a pair of calciferous glands in nine. We also provide an updated key for all genera of Ocnerodrilidae.